An institutional view on access to finance by Tanzanian women-owned enterprises. Issue 2 (3rd April 2018) - Naegels, Vanessa; Mori, Neema; D'Espallier, Bert
Abstract: We investigate the limited use of bank and microfinance loans by Tanzanian female entrepreneurs. Using survey data, we observe that female entrepreneurs mainly use informal sources to finance their businesses. We analyze how "perceptions" of gendered cognitive and normative institutions determine whether a female entrepreneur applies for a formal loan. Following results stand out: first, we find that high collateral requirements, interest rates and personal guarantee requirements make formal loans unattractive. Second, female entrepreneurs only apply when they expect to be successful. Since they "perceive" access to finance to be more problematic for women, female entrepreneurs are discouraged from applying. Third, female entrepreneurs "perceive" they have insufficient access to financial knowledge which again will prevent them from applying. This study contributes to theory by exploring the effect of entrepreneurs' perceptions of the institutional business environment on financing behavior. Furthermore, we show that the low use of formal loans by female entrepreneurs is primarily demand-driven, which calls into question the effectivity of policy recommendations aiming to increase supply of formal loans.